EFEKTIFITAS EKSTRAK BUAH SONNERATIA ALBA TERHADAP AKTIFITAS BAKTERI - Deny Kurniawan (Jurnal Harpodon Borneo, 2017)
Sonneratia alba is a mangrove species that is widely available in Indonesia. Phytochemical studies on Sonneratia alba showed that this plant is very potential as an anti-fungal, especially in the bark. However, few studies on the utilization of the fruit of S. alba. Therefore, required a study of phytochemicals from fruit S. alba which may be useful as an antibacterial. The process of this research is a fruit extraction using maceration method terraced ie the fraction of n-hexane, ethyl acetate and ethanol. The results maceration then tested the phytochemicals in order to know the content of the active compounds in the fruit of S. alba. Then, each fraction is tested antibacterial activity. Based on the results obtained by maceration extract of S. alba yield on the solvent n-hexane amounted to 3.17%, the solvent ethyl acetate by 1.91% and amounted to 8.69% ethanol. Phytochemical screening results, the solvent n-hexane contained alkaloids and flavonoids, ethyl acetate solvent contained alkaloids, steroids and flavonoids and flavonoid compounds contained ethanol and carbohydrate. Antibacterial test results and inhibition zone measuring results, the three extracts of S. alba is n-hexane, ethyl acetate and ethanol has potential as an antibacterial against Streptococcus mutans, Propionibacterium acnes, and Candida albicans. Keywords: Sonneratia alba, phytochemicals, antibacterial